Effects of erbium oxide addition on physical and optical properties of willemite-based glass ceramic sintered at different temperatures - Sarrigani, Gholamreza Vahedi (2014)
Zinc silicate glass is an attractive host matrix for rare-earth ions because of its fine properties, primarily optical and mechanical properties, such as good chemical stability, high UV transparency, high surface damage threshold, large tensile fracture strength and good durability. Up to now most research has been carried out on soda lime silicate (SLS) glass doped with different ingredients and rare-earths, but a few researches have been carried out on willemite-based glass-ceramic prepared using waste material and doped with erbium oxide (Er2O3). However; using waste materials such as SLS glass as a main source for producing silicate will be economical, cheap and helpful for reducing the aggregation of waste materials from the landfill. The main objective of this study is to determine the effect of erbium oxide (Er2O3) addition on physical and optical properties of willemite-base glass ceramic sintered at different temperatures. The samples were produced via melt-quenching technique followed by powdering, pressing and sintering. In the first stage the SLS glasses were crushed, grounded, and sieved to gain the expected particle size. The prepared powder was mixed with ZnO followed by melting at the temperature of 1400 °C and quenching in water to obtain fritz glass. The prepared fritz glass was crushed using mortar and pestle to the size of 63 μm. After that the prepared powder was heat treated at the temperature of 1000 °C to produce willemite. The willemite-based glass ceramic was doped with trivalent erbium (Er3+) in the ([(ZnO)0.5(SLS)0.5]1-x[Er2O3]x) composition where x = 1-5 wt.%. At the end, the powder was pressed and different pallets were prepared and finally sintered at different temperature ranged from 500 to1100 °C. The crystal (phase) changes with different contents of Er2O3 and different sintering temperatures were investigated using X-ray diffraction (XRD); the binding structure was explored by Fourier transform infrared spectroscopy (FTIR); the microstructure, morphology and chemical composition were be studied using Field emission scanning electron microscopy (FE-SEM) along with EDAX; and the optical properties was analyzed by UV-VIS spectroscopy. The XRD results show that well crystalline willemite (Zn2SiO4) with the contribution of dopant (Er3+) in the lattice can be achieved at the temperature of 900 °C. The XRD results also shows that rhombohedra crystalline willemite was formed by mixing ZnO and SLS glass and optimum heat treatment of 1000 °C to produce willemite-based glass ceramics, the solid-state reaction between well crystallized willemite and Er3+ was obtained at 900 °C sintering temperature and Er3+ can be completely dissolved in the lattice at this temperature. FTIR results confirmed the appearance of the vibrations of SiO4 and ZnO4 groups which clearly suggests the formation of the Zn2SiO4 phase, the compositional evaluation of the FTIR properties of the [(ZnO)0.5(SLS)0.5]1-x[Er2O3]x system indicates that the presence of erbium ions affects the surrounding of the Si-O and trivalent erbium occupy their position, these agrees with the XRD data at the peak positioned at 20.29°. The most significant modification produced by the addition of erbium and the increase of the heat treatment temperature of the studied samples shows a drop in the intensity of FTIR band located at 513 cm-1, which indicates that the addition of erbium oxide and increase in the sintering temperature declines the presence of SiO4 group. The micro structure analysis of the samples using FESEM shows that the average grain size of samples tends to increase from 325.29 to 625.2 nm as the sintering temperature increases. Finally, the UV-VIS spectra of all doped glass-ceramics depict absorption band due to host matrix network and the presence of Er2O3. The results show that the intensity of the bands tends to grow by increasing the Er2O3 content in the range of 1-5 wt.%, and the sintering temperature in the 500-900 °C range, followed by a drop at the temperatures of 1000 and 1100 °C. By adding the Er2O3 content to the host network and increasing the sintering temperature from 500-900 °C , the intensity of UV-VIS bands situated between 400-1800 nm increased due to the absorption of Er3+ions and the host crystal structure. The intensity of the UV bands were observed to have dropped when the sintering temperature was increased to 1000 and 1100 °C, which indicates that by going to the temperature of 1000 and 1100 °C the Er2O3 particles tend to produce cluster that causes the decrease in the UV absorption bands. For the sample with x=5 wt.% Er2O3, two strong absorption bands situated at about 1535 and 523 nm were observed. These bands were attributed to the optical transition from 4I15/2 to 4I13/2 and 4S3/2 state respectively.